Evaluation of food offered in schools and bought by students in Rzeszów - Momora, Agnieszka; Mazur, Artur; Dereń, Katarzyna (European Journal of Clinical and Experimental Medicine, 2018)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. According to epidemiologic research, the number of obese and overweight children is increasing. A common way of dealing with this problem is enacting legislation regarding food served in educational institutions. In Poland, the regulations regarding the assortment of school shops are contained in the Ordinance of the Minister of Health of 26th June 2015 (and its subsequent amendments). <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The main aim of this study is to evaluate the product range of school shops and vending machines in Rzeszów. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Method and materials. The study covered 52 primary and secondary schools in Rzeszów. The schools included in the study had 15568 students altogether. Products bought by students in school shops and vending machines were recorded over the period of 3 days. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The study has shown a statistically significant relationship (p <0.001) between the amount and types of products bought in primary and secondary schools. Healthy snacks only made up a small percentage of products sold. Secondary schools sold 20% more snacks with high sugar content compared to primary schools. A majority of products sold were compliant with regulations (p=0.12). <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. The assortment of school shops has changed after the implementation of the Ordinance of the Minister of Health of 26 June 2015 (and its subsequent amendments). The newly introduced restrictions significantly narrowed down the range of products offered in schools, reducing the number of products containing more than 15g of sugar (13.5g per 100g/ml in case of dairy products) or 10g of fat per portion.